(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2016)
The aim of this work is to demonstrate that, in the case of free legal transactions, once the impenetrable clause has been affixed, it must prevail, even if article 184 of the National Tax Code and article 30 of the Tax Enforcement Law say otherwise.